Novice Chinese as a foreign language teachers’ identity construction in primary schools in New Zealand from positioning and affordance perspectives - Sun, Peijian Paul; Wang, Yawen; Lv, Yanxing; Li, Zhishan (Frontiers in Psychology, 2022)
While there is a rapid increase of students learning Chinese as a foreign language (CFL) worldwide, limited attention has been drawn to CFL teachers’ positioning and affordances to interpret their identity construction in an overseas context. To fill the gap, this study investigated seven novice CFL teachers’ identity construction as Chinese language teachers in primary schools in New Zealand from positioning and affordance perspectives. Retrospective semi-structured interviews were adopted to understand how the novice CFL teachers were positioned, how they positioned themselves, and what affordances they perceived to be influential to their Chinese language identity construction. The findings showed that the novice CFL teachers’ identity construction was subject to the social, institutional, and individual levels of being positioned, self-positioning, and affordances. Specifically, 1) consistent self-positioning at the social, institutional, and individual levels could largely determine the novice CFL teachers’ identity construction; 2) inconsistency of identities between being positioned and self-positioning at the social, institutional, and individual levels might weaken the novice CFL teachers’ identity construction; 3) affordances as opportunities at the social, institutional, and individual levels could strengthen the novice CFL teachers’ identity construction, whereas affordances as challenges could not. The study concluded with implications and limitations to inform future research.